Dia De Los Muertos - Lemons, Gary (Book collections on Project MUSE., 2016)
"Author's Note: I caught a ride to Oaxaca just in time for Día los Muertos. The afternoon after I arrived I was sitting in a small cafe an outdoor table in the shade drinking freshly squeezed orange juice--the things you remember--when across the plaza an old deeply brown woman began to dance--not a choreographed move but a fluid ageless spinning around the axis of her sandals--and as she moved she cried out--"de nada--de nada"--Over and over again. There were soldiers leaning against a wall also in the shade watching her and laughing but mostly people just walked by ignoring her. It was the last day of October 1969 and already under a harsh, unforgiving sun, the dead were staking terrain--moving in and around and through the apparently alive. This book comes out of these events but decades have passed since then. Therefore the poems are not intended to be in keeping with the feeling qualities of Mexico today. The Mexico of today is--regrettably--a place I don't know. Día los Muertos is--rather--like the bones of a giant beast dug out of a tar pit then reassembled. It must poorly represent the living creature. The book still feels to me like the migration of a prayer or perhaps a curse uttered millions of years ago by the first creature misunderstanding the essential interaction of magic and mortality"--